Estudo dos Campopleginae (Hymenoptera, Ichneumonidae) neotropicais com ênfase na fauna da Mata Atlântica, Brasil - Onody, Helena Carolina (Universidade Federal de São Carlos, 2005)
The material used in this study comes from the projects: "Biodiversidade de Isoptera e Hymenoptera" (BIOTA/FAPESP), "Diversidade da fauna de Braconidae (Hymenoptera) em diferentes altitudes em Campos do Jordão, São Paulo, Brasil (CNPq) and from brazilian collections. This work has for main objectives a survey of the Campopleginae fauna in Brazil and to know its distribution throughout latitudinal and altitudinal gradients in areas of Atlantic Forest. Using Malaise traps, Moericke traps and sweeping the vegetation were obtained a total of 7.550 specimens identified and distributed in 19 genera. The genus Enytus was for the first time cited to Brazil and a new genus was identified. Microcharops, Casinaria, Dusona and Nonnus were the most common genera. Studying the Campopleginae throughout a latitudinal gradient, in eighteen localities of Atlantic Forest, the higher values of abundance, species richness and diversity were recorded in the Brazilians regions South and Southeast. The results indicated the reduction of the abundance, diversity and species richness of this subfamily in direction the localities of lower latitudes. In the analysis of the diversity of the fauna of the Campopleginae throughout an altitudinal gradient in other area of Atlantic Forest (Campos do Jordão, SP), the higher number of specimens was evidenced in mid altitudes. The diversity and the species richness showed a strong influence of the climate. The results of this study extend the knowledge on the distribution of the Campopleginae in Neotropical region and contribute for studies on distribution of parasitoid insects throughout latitudinal and altitudinal gradients.
Keywords: Ichneumonoidea; Mata Atlântica; Diversidade biológica; Campopleginae; CIENCIAS BIOLOGICAS::ECOLOGIA